Proposed Voltage Vector to Optimize Efficiency of Direct Torque Control - Goh Wee Yen; Ali Monadi; Nik Rumzi Nik Idris; Auzani Jidin; Tole Sutikno (Institute of Advanced Engineering and Science, 2014)
Compared to field-oriented control (FOC) system, direct torque control (DTC) system has gained attractiveness in control drive system because of its simpler control structure and faster dynamic control. However, supplying the drive system with rated flux at light load will decrease the power factor and efficiency of the system. Thus, an optimal flux has been applied during steady-state in order to maximize the efficiency of drive system. But when a torque is suddenly needed, for example during acceleration, the dynamic of the torque response would be degraded and it is not suitable for electric vehicle (EV) applications. Therefore, a modification to the voltage vector as well as look-up table has been proposed in order to improve the performance of torque response.DOI: http://dx.doi.org/10.11591/ijpeds.v4i4.6918